Nickel phosphide / nitrogen-phosphorus doped carbon nanosheet composite electrode material and preparation method and application thereof

By preparing nickel phosphide/nitrogen-phosphorus doped carbon nanosheet composite electrode materials, the problem of low conductivity of metal complex electrode materials is solved, and the rate performance and cycle stability are significantly improved, and its application performance in the fields of new energy storage and conversion is improved.

CN119517638AActive Publication Date: 2025-02-25QILU UNIVERSITY OF TECHNOLOGY (SHANDONG ACADEMY OF SCIENCES)
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
CN202411759506.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-03
Publication Date
2025-02-25
Estimated Expiration
2044-12-03

AI Technical Summary

Technical Problem

The low conductivity of existing metal complex electrode materials leads to insufficient rate performance and cycling stability, limiting their application in metal-air batteries and supercapacitors.

Method used

A composite electrode material of nickel phosphide/nitrogen-phosphorus doped carbon nanosheets is used to mix the organic solvent solution of metal salt with ligand and surfactant to obtain a precursor solution. After solvothermal reaction and calcination, nitrogen-phosphorus doped carbon nanosheets supported by nickel phosphide are prepared.

Benefits of technology

The conductivity and rate performance of the electrode material is improved, volume stability and cyclic stability are enhanced, and its performance in oxygen reduction reactions and supercapacitors is significantly improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119517638A_ABST
    Figure CN119517638A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of electrode materials, and particularly relates to a nickel phosphide / nitrogen-phosphorus-doped carbon nanosheet composite electrode material and a preparation method and application thereof.The composite electrode material comprises a nitrogen-phosphorus-doped carbon nanosheet and nickel phosphide loaded on the nitrogen-phosphorus-doped carbon nanosheet, the specific surface area of the composite electrode material is 663-1587 cm <-2 > g <-1 >, the aperture size is 1.2-8 nm, the content of C is 94.5-96 at.%, the content of N is 0.4-1.5 at.%, the content of P is 0.1-0.8 at.%, the content of O is 2.5-3.3 at.%, and the content of Ni is 0.1-1 at.%, the composite electrode material can show good stability in the electrochemical process, can maintain high performance for a long time, and prolongs the service life of a supercapacitor.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of electrode materials, and more specifically, to a composite electrode material of nickel phosphide / nitrogen and phosphorus doped carbon nanosheets and a preparation method and application thereof. Background Art

[0002] With the continuous consumption of non-renewable energy around the world, environmental pollution is becoming more and more serious, leading to an increasingly urgent demand for clean, renewable and sustainable new energy. Therefore, the research on new energy storage devices is important and of great significance. Among them, metal-air batteries have attracted much attention due to their high energy density, low price, abundant reserves and low environmental pollution. However, the main factors restricting the development of metal-air batteries are the catalytic activity, selectivity and stability of the catalyst required for the positive electrode oxygen reduction reaction.

[0003] Metal complexes have high theoretical capacity and low cost, and are theoretical materials for making battery electrode materials. And because of the simple synthesis process and easy availability of raw materials, they are widely used in the fields of photocatalytic water splitting, hydrogen storage, catalyst materials, etc. However, this type of material has low conductivity, which reduces its rate performance as an electrode material; in addition, during the electrochemical reaction, its volume changes severely, which greatly reduces its cycle stability as an electrode material. Summary of the invention

[0004] The present application is provided to solve the above defects existing in the prior art. A composite electrode material of nickel phosphide / nitrogen phosphorus doped carbon nanosheets and its preparation method and application are needed, which can improve the conductivity and rate performance compared with metal complexes, and have good volume stability and cycle stability during use.

[0005] In a first aspect of the present application, a composite electrode material of nickel phosphide / nitrogen and phosphorus doped carbon nanosheets is provided, wherein the composite electrode material comprises nitrogen and phosphorus doped carbon nanosheets and nickel phosphide supported on the nitrogen and phosphorus doped carbon nanosheets, and the specific surface area of ​​the composite electrode material is 663-1587 cm -2 g -1 , pore size of 1.2-8 nm, C content of 94.5-96 at. %, N content of 0.4-1.5 at. %, P content of 0.1-0.8 at. %, O content of 2.5-3.3 at. % and Ni content of 0.1-1 at. %.

[0006] In the second aspect of the present application, a method for preparing a composite electrode material of nickel phosphide / nitrogen and phosphorus doped carbon nanosheets as described in any embodiment of the present application is provided, the preparation method comprising: mixing an organic solvent solution of a metal salt with a ligand and a surfactant to obtain a precursor solution; subjecting the precursor solution to a solvothermal reaction to obtain a metal complex; and calcining the metal complex and a phosphorus source in a tubular furnace to obtain a composite electrode material.

[0007] The third aspect of the present application provides an application of the composite electrode material of nickel phosphide / nitrogen and phosphorus doped carbon nanosheets described in any embodiment of the present application and / or the preparation method described in any embodiment of the present application in the preparation of ORR catalyst electrodes.

[0008] The fourth aspect of the present application provides an application of the composite electrode material of nickel phosphide / nitrogen and phosphorus doped carbon nanosheets described in any embodiment of the present application and / or the preparation method described in any embodiment of the present application in the preparation of supercapacitor electrodes.

[0009] The nickel phosphide / nitrogen and phosphorus doped carbon nanosheet composite electrode material and its preparation method and application provided in each embodiment of the present application are prepared by an organic solvent solution of a raw metal salt and a ligand and a surfactant to obtain a metal complex, and then pyrolyzed to obtain a composite electrode material, forming a special structure of nitrogen and phosphorus doped carbon nanosheets, and also loaded with nickel phosphide; the composite electrode material can exhibit excellent catalytic activity and electrochemical performance. The composite electrode material has a specific electrochemical performance of 1 A g -1 At a current density of 1.5 Å, its specific capacitance is as high as 300 F g -1 The above; metal organic ligand derived carbon materials show good stability in the electrochemical process, can maintain high performance for a long time, and extend the service life of supercapacitors. The advantages brought to the oxygen reduction reaction in terms of structure and other aspects have broad application prospects. In addition, the preparation method of the present application adopts the simultaneous carbonization and phosphation of metal complexes, which simplifies the preparation process of nickel phosphide; and the preparation method has the advantages of low raw material price, wide source, simple preparation process, and easy industrialization. BRIEF DESCRIPTION OF THE DRAWINGS

[0010] In the drawings, which are not necessarily drawn to scale, the same reference numerals may describe similar components in different views. The drawings generally illustrate various embodiments by way of example and not limitation, and together with the specification and claims, are used to illustrate the claimed embodiments. When appropriate, the same reference numerals are used throughout the drawings to refer to the same or similar parts. Such embodiments are illustrative and are not intended to be exhaustive or exclusive embodiments of the present apparatus or method.

[0011] Figure 1The SEM image of the nickel phosphide / nitrogen and phosphorus doped carbon nanosheet composite electrode material prepared according to Example 1 of the present application is shown; Figure 2 The SEM image of the nickel phosphide / nitrogen and phosphorus doped carbon nanosheet composite electrode material prepared according to Example 2 of the present application is shown; Figure 3 The SEM image of the nickel phosphide / nitrogen and phosphorus doped carbon nanosheet composite electrode material prepared according to Example 3 of the present application is shown; Figure 4 The SEM image of the nickel phosphide / nitrogen and phosphorus doped carbon nanosheet composite electrode material prepared according to Example 4 of the present application is shown; Figure 5 The SEM image of the nickel phosphide / nitrogen and phosphorus doped carbon nanosheet composite electrode material prepared according to Comparative Example 1 of the present application is shown; Figure 6 The SEM image of the nickel phosphide / nitrogen and phosphorus doped carbon nanosheet composite electrode material prepared according to Comparative Example 2 of the present application is shown. DETAILED DESCRIPTION

[0012] In order to enable those skilled in the art to better understand the technical solution of the present application, the present application is described in detail below in conjunction with the accompanying drawings and specific implementation methods. The embodiments of the present application are further described in detail below in conjunction with the accompanying drawings and specific implementation methods, but are not intended to limit the present application.

[0013] The words "first", "second" and similar words used in this application do not indicate any order, quantity or importance, but are only used to distinguish. The words "include" or "comprise" and similar words mean that the elements before the word include the elements listed after the word, and do not exclude the possibility of including other elements.

[0014] According to an embodiment of the present application, a composite electrode material of nickel phosphide / nitrogen and phosphorus doped carbon nanosheets is provided, wherein the composite electrode material comprises nitrogen and phosphorus doped carbon nanosheets and nickel phosphide supported on the nitrogen and phosphorus doped carbon nanosheets, and the specific surface area of ​​the composite electrode material is 663-1587 cm -2 g -1 , pore size is 1.2-8 nm, C content is 94.5-96 at. %, N content is 0.4-1.5 at. %, P content is 0.1-0.8 at. %, O content is 2.5-3.3 at. % and Ni content is 0.1-1 at. %, where at. % means atomic percentage.

[0015] Using nitrogen and phosphorus doped carbon nanosheets as a skeleton to support nickel phosphide can prevent particle agglomeration and structural collapse, which is beneficial to improving the electrochemical properties of the material.

[0016] Metal organic ligand derived carbon nanosheet materials show good stability in electrochemical processes, can maintain high performance for a long time, and extend the service life of supercapacitors. The advantages brought to oxygen reduction reactions in terms of the structure of carbon nanosheets. The special structure formed by metal ions and organic ligands in metal organic ligand derived carbon materials at high temperatures provides abundant active sites for oxygen reduction reactions, thereby improving catalytic activity.

[0017] Carbon materials themselves have good corrosion resistance, and metal organic ligand-derived carbon materials not only maintain this advantage, but also further enhance their corrosion resistance through the introduction of metal ions, enabling them to maintain efficient catalytic performance in harsh environments.

[0018] In some embodiments, the nickel phosphide in the composite electrode material includes NiP, Ni5P4, NiP2 and Ni 12 One or more of P5.

[0019] According to the embodiments of the present application, there is also provided a method for preparing a composite electrode material of nickel phosphide / nitrogen and phosphorus doped carbon nanosheets as described in any embodiment of the present application, the preparation method comprising: mixing an organic solvent solution of a metal salt with a ligand and a surfactant to obtain a precursor solution; subjecting the precursor solution to a solvothermal reaction to obtain a metal complex; and calcining the metal complex and a phosphorus source in a tubular furnace to obtain a composite electrode material.

[0020] In this application, a metal salt and a ligand are first reacted in an environment of an organic solvent and a surfactant to obtain a precursor, the precursor undergoes a solvothermal reaction to obtain a metal complex, and the metal complex is pyrolyzed to obtain a composite electrode material. Metal organic ligands have a periodic crystal structure and high porosity, and the size, composition and structure of the derived carbon can be regulated by pyrolysis. This structural controllability allows the prepared carbon material to have a more uniform pore structure distribution and a higher porosity, which is beneficial to its application in the field of electrochemistry.

[0021] The organic part in the metal organic ligand will be cracked and converted into carbon material at high temperature, while the metal ions can be oxidized or reduced and evenly distributed in the carbon matrix. This structure can not only inhibit the agglomeration of metals, but also enhance the interaction between metals and carbon materials, thereby improving the overall performance of the material. Therefore, the preparation of carbon materials by carbonization of metal ligands not only improves the structural controllability and performance optimization of carbon materials, but also brings many advantages to application fields such as supercapacitors and oxygen reduction reactions.

[0022] The organic solvent and the surfactant play a dispersing role. In the process of obtaining the precursor, they can help to obtain the structure of the carbon nanosheets and the uniform pore structure and higher porosity after calcination.

[0023] In some embodiments, the organic solvent is DMF (N,N-dimethylformamide); the ligand is at least one of nitrophthalic acid and phthalic acid; and the surfactant is nitrilotriacetic acid. Different types of ligands result in different physical properties of the obtained composite electrode materials, such as different specific surface areas and pore sizes. Surfactants are beneficial for making the composite electrode materials have higher specific surface areas and better pore structures.

[0024] In some embodiments, the mass volume ratio of the metal salt, ligand, surfactant and organic solvent in the precursor solution is: (0.45-1.53) g: (0.1-0.8) g: (0.06-0.2) g: (30-50) mL. Under different ratios, the physical structure of the obtained composite electrode material is different, which in turn affects the oxygen reduction catalytic performance and supercapacitor performance of the composite electrode material.

[0025] In some embodiments, the conditions of the solvent thermal reaction are: temperature 110-200°C, time 1-10 hours. Preferably, the conditions of the solvent thermal reaction are: temperature 110-140°C, time 6-10 hours In some embodiments, the calcination conditions are: temperature 800-1500° C., time 1-10 hours. Different calcination temperatures result in different physical properties of the obtained composite electrode material, such as different specific surface areas and pore sizes.

[0026] In some embodiments, the phosphorus source is sodium hypophosphite.

[0027] According to the embodiments of the present application, there is also provided an application of the composite electrode material of nickel phosphide / nitrogen and phosphorus doped carbon nanosheets described in any embodiment of the present application and / or the preparation method described in any embodiment of the present application in the preparation of ORR catalyst electrodes.

[0028] According to the embodiments of the present application, there is also provided an application of the composite electrode material of nickel phosphide / nitrogen and phosphorus doped carbon nanosheets described in any embodiment of the present application and / or the preparation method described in any embodiment of the present application in the preparation of supercapacitor electrodes.

[0029] The composite electrode material obtained in the present application has applications in oxygen reduction catalysis and also has applications in supercapacitors.

[0030] Example 1 (1) Add 0.45 g zinc chloride and 0.01 g nickel chloride to a beaker, then add 30 mL DMF and stir to dissolve the metal salts, then add 0.10 g phthalic acid and 0.06 g nitrilotriacetic acid and stir to form a uniform precursor solution; (2) transferring the precursor solution described in step (1) to a reaction kettle and performing a solvothermal reaction at a reaction temperature of 110° C. for a reaction time of 10 hours. After cooling to room temperature, the product is filtered and washed with ethanol. The product is then dried at a temperature of 50° C. for a drying time of more than 24 hours to obtain a metal complex. (3) The metal complex prepared in step (2) is placed in a tubular furnace, and sodium hypophosphite is placed at the air inlet. The complex is calcined in an argon atmosphere at a temperature of 800° C. for 10 hours to obtain a nickel phosphide / nitrogen and phosphorus doped carbon nanosheet composite electrode material.

[0031] The prepared nickel phosphide / nitrogen and phosphorus doped carbon nanosheet composite electrode material was subjected to SEM detection. Figure 1 The SEM image and test analysis show that the specific surface area of ​​the prepared nickel phosphide / nitrogen and phosphorus doped carbon nanosheet composite electrode material is 663 cm -2 g -1 The pore size is 1.2 nm. The prepared composite electrode material has a C content of 94.5 at.%, a N content of 1.5 at.%, a P content of 0.5 at.%, an O content of 3.4 at.%, and a Ni content of 0.1 at.%.

[0032] Example 2 (1) Add 1.00 g zinc chloride and 0.02 g nickel chloride to a beaker, then add 30 mL DMF and stir to dissolve the metal salts, then add 0.20 g phthalic acid, 0.20 g nitrophthalic acid and 0.08 g nitrilotriacetic acid and stir to form a uniform precursor solution; (2) transferring the precursor solution described in step (1) to a reaction kettle and performing a solvothermal reaction at a reaction temperature of 120° C. for a reaction time of 8 hours. After cooling to room temperature, the product is filtered and washed with ethanol. The product is then dried at a temperature of 50° C. for a drying time of more than 24 hours to obtain a metal complex. (3) The metal complex prepared in step (2) is placed in a tubular furnace, and sodium hypophosphite is placed at the air inlet. The complex is calcined in an argon atmosphere at a temperature of 900° C. for 5 hours to obtain a nickel phosphide / nitrogen and phosphorus doped carbon nanosheet composite electrode material.

[0033] The prepared nickel phosphide / nitrogen and phosphorus doped carbon nanosheet composite electrode material was subjected to SEM detection. Figure 2 The SEM image and test analysis show that the specific surface area of ​​the prepared nickel phosphide / nitrogen and phosphorus doped carbon nanosheet composite electrode material is 851 cm -2 g -1The pore size is 7 nm. The prepared composite electrode material has a C content of 94.8 at.%, a N content of 0.8 at.%, a P content of 0.8 at.%, an O content of 3.3 at.%, and a Ni content of 0.3 at.%.

[0034] Example 3 (1) Add 1.50 g zinc chloride and 0.03 g nickel chloride to a beaker, then add 50 mL DMF and stir to dissolve the metal salts, then add 0.80 g nitrophthalic acid and 0.20 g nitrilotriacetic acid and stir to form a uniform precursor solution; (2) transferring the precursor solution described in step (1) to a reaction kettle, and performing a solvothermal reaction at a reaction temperature of 140° C. for a reaction time of 6 hours. After cooling to room temperature, the product is filtered, and the filtered product is washed with ethanol, and then dried at a temperature of 50° C. for a drying time of more than 24 hours to obtain a metal complex; (3) The metal complex prepared in step (2) is placed in a tubular furnace, and sodium hypophosphite is placed at the air inlet. The complex is calcined in an argon atmosphere at a temperature of 1000° C. for 4 hours to obtain a nickel phosphide / nitrogen and phosphorus doped carbon nanosheet composite electrode material.

[0035] The prepared nickel phosphide / nitrogen and phosphorus doped carbon nanosheet composite electrode material was subjected to SEM detection. Figure 3 The SEM image and test analysis show that the specific surface area of ​​the prepared nickel phosphide / nitrogen and phosphorus doped carbon nanosheet composite electrode material is 1587 cm -2 g -1 The pore size is 6 nm. The prepared composite electrode material has a C content of 94.5 at.%, a N content of 1.2 at.%, a P content of 0.7 at.%, an O content of 3.3 at.%, and a Ni content of 0.3 at.%.

[0036] Example 4 (1) Add 1.50 g of magnesium chloride and 0.03 g of nickel chloride to a beaker, then add 50 mL of DMF and stir to dissolve the metal salts. Then add 0.80 g of nitrophthalic acid and 0.20 g of nitrilotriacetic acid and stir to form a uniform precursor solution. (2) transferring the precursor solution described in step (1) to a reaction kettle and performing a solvothermal reaction at a reaction temperature of 140° C. for a reaction time of 6 hours. After cooling to room temperature, the solution is filtered and the product obtained by filtration is washed with ethanol. The product is then dried at a temperature of 50° C. for a drying time of more than 24 hours to obtain a metal complex. (3) The metal complex prepared in step (2) is placed in a tubular furnace, and sodium hypophosphite is placed at the air inlet. The complex is calcined in an argon atmosphere at a temperature of 1500° C. for 3 hours to obtain a nickel phosphide / nitrogen and phosphorus doped carbon nanosheet composite electrode material.

[0037] The prepared nickel phosphide / nitrogen and phosphorus doped carbon nanosheet composite electrode material was subjected to SEM detection. Figure 4 The SEM images and test analysis show that the specific surface area of ​​the prepared nickel phosphide / nitrogen and phosphorus doped carbon nanosheet composite electrode material is 1312 cm -2 g -1 The pore size is 8 nm. The prepared composite electrode material has a C content of 96.0 at.%, a N content of 0.4 at.%, a P content of 0.1 at.%, an O content of 2.5 at.%, and a Ni content of 1.0 at.%.

[0038] The calcination temperatures and calcination times of step (3) in Example 3 and Example 4 are different, and the specific surface areas and pore sizes of the obtained composite electrode materials are different.

[0039] Comparative Example 1 (1) Add 0.45 g zinc chloride and 0.01 g nickel chloride to a beaker, then add 30 mL DMF and stir to dissolve the metal salts, then add 0.10 g phthalic acid and stir to form a uniform precursor solution; (2) transferring the precursor solution described in step (1) to a reaction kettle and performing a solvothermal reaction at a reaction temperature of 110° C. for a reaction time of 10 hours. After cooling to room temperature, the solution is filtered and the product obtained by filtration is washed with ethanol. The product is then dried at a temperature of 50° C. for a drying time of more than 24 hours to obtain a metal complex. (3) The metal complex prepared in step (2) is placed in a tubular furnace, and sodium hypophosphite is placed at the air inlet. The complex is calcined in an argon atmosphere at a temperature of 800° C. for 10 hours to obtain a nickel phosphide / nitrogen and phosphorus doped carbon nanosheet composite electrode material.

[0040] The prepared nickel phosphide / nitrogen and phosphorus doped carbon nanosheet composite electrode material was subjected to SEM detection. Figure 5 The SEM image shown and the test analysis show that the specific surface area of ​​the prepared nickel phosphide / nitrogen and phosphorus doped carbon nanosheet composite electrode material is 564 cm -2 g -1 The pore size is 2 nm. The prepared composite electrode material has a C content of 92.9 at.%, a N content of 0.8 at.%, an O content of 5.8 at.% and a Ni content of 0.5 at.%.

[0041] Comparative Example 2 (1) Add 1.50 g zinc chloride and 0.03 g nickel chloride to a beaker, then add 50 mL DMF and stir to dissolve the metal salts, then add 0.80 g nitrophthalic acid and stir to form a uniform precursor solution; (2) transferring the precursor solution described in step (1) to a reaction kettle and performing a solvothermal reaction at a reaction temperature of 140° C. for a reaction time of 6 hours. After cooling to room temperature, the solution is filtered and the product obtained by filtration is washed with ethanol. The product is then dried at a temperature of 50° C. for a drying time of more than 24 hours to obtain a metal complex. (3) The metal complex prepared in step (2) is placed in a tubular furnace, and sodium hypophosphite is placed at the air inlet. The complex is calcined in an argon atmosphere at a temperature of 1000° C. for 4 hours to obtain a nickel phosphide / nitrogen and phosphorus doped carbon nanosheet composite electrode material.

[0042] The prepared nickel phosphide / nitrogen and phosphorus doped carbon nanosheet composite electrode material was subjected to SEM detection. Figure 6 The SEM image and test analysis show that the specific surface area of ​​the prepared nickel phosphide / nitrogen and phosphorus doped carbon nanosheet composite electrode material is 336 cm -2 g -1 The pore size is 1.5 nm. The prepared composite electrode material has a C content of 95.4 at.%, a N content of 0.2 at.%, a P content of 2.8 at.%, an O content of 1.5 at.%, and a Ni content of 0.1 at.%.

[0043] In Comparative Examples 1 and 2, no surfactant was added, and the obtained composite electrode materials had a smaller specific surface area and a smaller pore size. Figure 5 and Figure 6 , and Figure 1 and Figure 3 By comparison, it can be seen that the structure of carbon nanosheets was not prepared in Comparative Example 1 and Comparative Example 2, and spherical particles were obtained in Comparative Example 1. Block or rod-like structures were obtained in Comparative Example 2. Therefore, the raw materials of the present application cooperate with the materials to obtain the special structure of carbon nanosheets.

[0044] Preparation of ORR catalyst electrode The electrode materials prepared in Examples 1-4 and Comparative Examples 1-2 were prepared into ORR catalyst electrodes using the method in the literature (Nano Energy 2021, 85, 106024.). The oxygen reduction electrocatalytic performance of the prepared ORR catalyst electrodes was tested, and the test analysis results are shown in Table 1.

[0045] It can be seen from Table 1 that the oxygen reduction half-wave potential E of the electrode materials of Examples 1-4 is 1 / 2 and oxygen reduction limiting current density J limited It is significantly greater than that of Comparative Examples 1-2. The Tafel slope of the electrode materials of Examples 1-4 is significantly less than that of Comparative Examples 1-2, indicating that the electrode materials prepared by the present invention have a higher oxygen reduction catalytic activity and faster oxygen reduction reaction kinetics. This is due to the higher specific surface area, suitable pore size and higher heteroatom content of the electrode material. The oxygen reduction catalytic performance of the composite electrode materials obtained by different ratios and different preparation conditions in Examples 1-4 is different. The oxygen reduction catalytic performance of the composite electrode materials of Comparative Examples 1 and Comparative Examples 2 is weaker than that of Examples 1-4, indicating that the preparation method of the present application can obtain a composite electrode material with better oxygen reduction catalytic performance.

[0046] Table 1 Oxygen reduction catalytic performance of electrode materials prepared in Examples 1-4 and Comparative Examples 1-2 Preparation of supercapacitor electrodes The electrode materials prepared in Examples 1-4 and Comparative Examples 1-2 were prepared into supercapacitor electrodes using the preparation method described in the literature (Applied Surface Science 2020, 533, 147511.). The electrochemical properties of the prepared supercapacitor electrodes were tested, and the test analysis results are shown in Table 2.

[0047] Compared with Table 2, it can be seen that after 10,000 cycles of charge and discharge, the specific capacitance of the electrode materials of Examples 1-4 is still maintained at 300 F g -1 The capacity retention rates are all above 95%, which is significantly greater than the specific capacitance of the electrode materials in Comparative Examples 1-2 (201-215 Fg -1 ) and capacity retention rate (85.9-87.6%). This shows that the electrode material has high charge storage capacity and stability. This is due to its high specific surface area, suitable pore size and high heteroatom doping.

[0048] Table 2 Supercapacitor performance of electrode materials prepared in Examples 1-4 and Comparative Examples 1-2 In addition, although exemplary embodiments have been described herein, the scope includes any and all embodiments based on the present application with equivalent elements, modifications, omissions, combinations (e.g., various embodiments intersecting schemes), adaptations or changes. The elements in the claims are to be interpreted broadly based on the language adopted in the claims, and are not limited to the examples described in this specification or during the practice of this application, and the examples are to be interpreted as non-exclusive. Therefore, this specification and examples are intended to be considered as examples only, and the true scope and spirit are indicated by the following claims and the full scope of their equivalents.

[0049] The above description is intended to be illustrative rather than restrictive. For example, the above examples (or one or more schemes thereof) may be used in combination with each other. For example, a person of ordinary skill in the art may use other embodiments when reading the above description. In addition, in the above-mentioned specific embodiments, various features may be grouped together to simplify the present application. This should not be interpreted as an intention that a feature of an application that does not require protection is necessary for any claim. On the contrary, the subject matter of the present application may be less than all the features of an embodiment of a particular application. Thus, the following claims are incorporated herein in the specific embodiments as examples or embodiments, wherein each claim is independently a separate embodiment, and it is considered that these embodiments may be combined with each other in various combinations or arrangements. The scope of the present invention should be determined with reference to the appended claims and the full scope of equivalent forms granted by these claims.

[0050] The above embodiments are only exemplary embodiments of the present application and are not intended to limit the present invention. The protection scope of the present invention is defined by the claims. Those skilled in the art may make various modifications or equivalent substitutions to the present invention within the essence and protection scope of the present application, and such modifications or equivalent substitutions shall also be deemed to fall within the protection scope of the present invention.

Claims

1. A composite electrode material of nickel phosphide / nitrogen and phosphorus doped carbon nanosheets, characterized in that: The composite electrode material comprises nitrogen and phosphorus doped carbon nanosheets and nickel phosphide supported on the nitrogen and phosphorus doped carbon nanosheets. The specific surface area of ​​the composite electrode material is 663-1587 cm -2 g -1 , pore size of 1.2-8 nm, C content of 94.5-96 at. %, N content of 0.4-1.5 at. %, P content of 0.1-0.8 at. %, O content of 2.5-3.3 at. % and Ni content of 0.1-1 at. %.

2. The composite electrode material according to claim 1, characterized in that The nickel phosphide in the composite electrode material includes NiP, Ni5P4, NiP2 and Ni 12 One or more of P5.

3. The method for preparing the composite electrode material of nickel phosphide / nitrogen and phosphorus doped carbon nanosheets according to claim 1, characterized in that: The preparation method comprises: mixing an organic solvent solution of a metal salt with a ligand and a surfactant to obtain a precursor solution; subjecting the precursor solution to a solvent thermal reaction to obtain a metal complex; and calcining the metal complex and a phosphorus source in a tubular furnace to obtain a composite electrode material.

4. The preparation method according to claim 3, characterized in that: The organic solvent is DMF; the ligand is at least one of nitrophthalic acid and phthalic acid; and the surfactant is nitrilotriacetic acid.

5. The preparation method according to claim 3, characterized in that: The mass volume ratio of the metal salt, ligand, surfactant and organic solvent in the precursor solution is: (0.46-1.53) g: (0.1-0.8) g: (0.06-0.2) g: (30-50) mL.

6. The preparation method according to claim 3, characterized in that: The conditions of the solvent thermal reaction are: temperature 110-200° C., time 1-10 hours.

7. The preparation method according to claim 3, characterized in that: The calcination conditions are: temperature 800-1500° C., time 1-10 hours.

8. The preparation method according to claim 3, characterized in that: The phosphorus source is sodium hypophosphite.

9. Use of the composite electrode material of nickel phosphide / nitrogen and phosphorus doped carbon nanosheets according to claim 1 and / or the preparation method according to any one of claims 3 to 8 in the preparation of ORR catalyst electrodes.

10. Use of the composite electrode material of nickel phosphide / nitrogen and phosphorus doped carbon nanosheets according to claim 1 and / or the preparation method according to any one of claims 3 to 8 in preparing supercapacitor electrodes.

Citation Information

Patent Citations

  • Transition metal phosphide / porous carbon anode composite material for sodium-ion battery and preparation method thereof

    CN105895886A

  • Phosphorus-nickel composite electrode material for supercapacitor or lithium battery and preparation method of phosphorus-nickel composite electrode material

    CN108878164A

  • Metal organic framework derived nitrogen-doped carbon nanosheet as well as preparation method and application thereof

    CN114220665A

  • Preparation method and application of nano metal phosphide

    CN115206688A

  • Preparation and application of nickel phosphide / porous graphitized nitrogen-doped carbon composite high-entropy van der Waals material

    CN117385410A